2010
DOI: 10.1016/j.matbio.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of embryonic tendon-like tissue by human marrow stromal/mesenchymal stem cells requires a three-dimensional environment and transforming growth factor β3

Abstract: Tendon-like tissue generated from stem cells in vitro has the potential to replace tendons and ligaments lost through injury and disease. However, thus far, no information has been available on the mechanism of tendon formation in vitro and how to accelerate the process. We show here that human mesenchymal stem cells (MSCs) and bone marrow-derived mononuclear cells (BM-MNCs) can generate tendon-like tissue in 7 days mediated by transforming growth factor (TGF) β3. MSCs cultured in fixed-length fibrin gels spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 60 publications
2
83
0
1
Order By: Relevance
“…This has been previously seen in MSC-seeded 3D constructs, by which the exposure of MSCs to a uniaxial force alone reduced the ''stemness'' of the seeded cells and left them unable to differentiate into osteogenic lineages after retrieval from the construct. 8 The maximum amount of time that the constructs could be maintained for before tearing off the pins was 14 days, as has been previously reported. 34 This limitation makes this model unsuitable for studying the longer-term effects of tissue development, but instead can be used to further analyze early-onset ESC differentiation and the associated molecular pathways.…”
Section: Figmentioning
confidence: 61%
See 3 more Smart Citations
“…This has been previously seen in MSC-seeded 3D constructs, by which the exposure of MSCs to a uniaxial force alone reduced the ''stemness'' of the seeded cells and left them unable to differentiate into osteogenic lineages after retrieval from the construct. 8 The maximum amount of time that the constructs could be maintained for before tearing off the pins was 14 days, as has been previously reported. 34 This limitation makes this model unsuitable for studying the longer-term effects of tissue development, but instead can be used to further analyze early-onset ESC differentiation and the associated molecular pathways.…”
Section: Figmentioning
confidence: 61%
“…4 Multiple studies have shown that TGF-b is up-regulated after tendon injury [5][6][7] and after their injection into the injured tendon, pluripotent equine embryo-derived stem cells (ESCs) express SCX. 5 The addition of TGF-b3 induces tenogenic differentiation of in vitro cultures of mesenchymal stem cells (MSCs), 8 micromass cultures of undifferentiated limb mesenchyme, 9 and equine ESCs. 5 Taken together, this suggests that TGF-b signaling plays a key role in triggering the initiation of tenocyte differentiation from stem cells and tendon progenitors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, we investigated the role of Egr1 in the formation of in vitro-engineered tendons. We used a 3D fibrin-based cell culture system that promotes tendon differentiation from primary chick tendon cells and human MSCs (30)(31)(32). C3H10T1/2-EGR1 cells cultured under uniaxial tension led to thicker tendon-like structures compared with C3H10T1/2 cells ( Figure 7, A and B).…”
Section: Egr1 Deficiency Affects Tendon Gene Expression During Achillmentioning
confidence: 99%